State-level seat belt use in the United States, 2011–2016: Comparison of self-reported with observed use and use by fatally injured occupants - Shakya, Iju (J Safety Res, 2020)
INTRODUCTION: Despite 49 states and the District of Columbia having seat belt laws that permit either primary or secondary enforcement, nearly half of persons who die in passenger vehicle crashes in the United States are unbelted. Monitoring seat belt use is important for measuring the effectiveness of strategies to increase belt use. OBJECTIVE: Document self-reported seat belt use by state seat belt enforcement type and compare 2016 self-reported belt use with observed use and use among passenger vehicle occupant (PVO) fatalities. METHODS: We analyzed the Behavioral Risk Factor Surveillance System (BRFSS) self-reported seat belt use data during 2011–2016. The Pearson correlation coefficient (r) was used to compare the 2016 BRFSS state estimates with observed seat belt use from state-based surveys and with unrestrained PVO fatalities from the Fatality Analysis Reporting System. RESULTS: During 2011–2016, national self-reported seat belt use ranged from 86–88%. In 2016, national self-reported use (87%) lagged observed use (90%) by 3 percentage points. By state, the 2016 self-reported use ranged from 64% in South Dakota to 93% in California, Hawaii, and Oregon. Seat belt use averaged 7 percentage points higher in primary enforcement states (89%) than in secondary states (82%). Self-reported state estimates were strongly positively correlated with state observational estimates (r = 0.80) and strongly negatively correlated with the proportion of unrestrained PVO fatalities (r = −0.77). CONCLUSION: National self-reported seat belt use remained essentially stable during 2011–2016 at around 87%, but large variations existed across states. PRACTICAL APPLICATIONS: If seat belt use in secondary enforcement states matched use in primary enforcement states for 2016, an additional 3.98 million adults would have been belted. Renewed attention to increasing seat belt use will be needed to reduce motor-vehicle fatalities. Self-reported and observational seat belt data complement one another and can aid in designing targeted and multifaceted interventions.